Energy Input Interaction in US Production - Copeland, Cassandra; Thompson, Henry (Review of Economic Analysis, 2022)
This paper estimates production functions with factor interaction for annual US output from 1949 to 2013 including energy Btu input with capital and labor. Interactions between the three factors are parsimoniously introduced to the error correction estimates. The findings are as follows: Fixed capital assets successfully control for technological change. Interaction between capital and energy reveal them to be very weak substitutes or complements. Factor price elasticities involving the labor force are strong. Labor is overpaid by 39% relative to its declining productivity, while energy is underpaid by 16% relative to its increasing productivity. The own wage effect is nearly elastic implying wage increases are met with nearly opposite percentage decreases in cost minimizing labor input.